Verification tests of a method of determining sound intensity with the application of a two microphone technique - Ryszard PANUSZKA; Jacek CIEŚLIK (Archives of Acoustics)
The paper presents several verification results of experimental tests. These tests led to the development of software and instrumentation for the method of measuring the acoustical intensity with the application of a two microphone technique. Results of a quantitative evaluation of chosen method errors occuring for the accepted for investigation pair of microphones were presented, as well as results of investigations leading to the evaluation of the accuracy of intensity measurements done with the developed measuring system.